2005
DOI: 10.1074/jbc.m507380200
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution 1H NMR-based Metabolomics Indicates a Neurotransmitter Cycling Deficit in Cerebral Tissue from a Mouse Model of Batten Disease

Abstract: The neuronal ceroid lipofuscinoses (NCLs) constitute a range of progressive neurological disorders primarily affecting children. Although six of the causative genes have been characterized, the underlying disease pathogenesis for this family of disorders is unknown. Using a metabolomics approach based on high resolution 1 H NMR spectroscopy of the cortex, cerebellum, and remaining regions of the brain in conjunction with statistical pattern recognition, we report metabolic deficits associated with juvenile NCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
108
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 45 publications
19
108
0
2
Order By: Relevance
“…Additionally, Cln3 Δex7/8 astrocytes show reduced expression of the glutamate transporter GLAST and glutamine synthetase, indicating altered glutamate recycling capacity, which supports the neurotransmitter imbalance associated with JNCL 6, 9, 10, 11. We have also reported that Cln3 Δex7/8 microglia are primed toward a proinflammatory phenotype when exposed to danger signals present in the Cln3 Δex7/8 brain 8.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Additionally, Cln3 Δex7/8 astrocytes show reduced expression of the glutamate transporter GLAST and glutamine synthetase, indicating altered glutamate recycling capacity, which supports the neurotransmitter imbalance associated with JNCL 6, 9, 10, 11. We have also reported that Cln3 Δex7/8 microglia are primed toward a proinflammatory phenotype when exposed to danger signals present in the Cln3 Δex7/8 brain 8.…”
Section: Resultssupporting
confidence: 61%
“…Prior reports using CLN3 knockout mice revealed heightened glutamate levels and reduced GABA in the cortex and cerebellum, and N‐methyl‐D‐aspartate or a‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptor blockade could improve motor function in these animals, lending support to the excitotoxic theory of neuronal loss in JNCL 10, 11, 33. Our recent work also supports this possibility, in that the expression of key molecules involved in glutamate clearance/detoxification from the synaptic cleft (GLAST and glutamine synthetase, respectively) were significantly reduced in the Cln3 Δex7/8 brain 6.…”
Section: Discussionmentioning
confidence: 80%
“…Although there are many platforms for metabolic profiling (for example, LC-MS, GC-MS, NMR, electrocapillary phoresis-MS), no one technology gives complete coverage of the metabonome. This technique has been used extensively in studies on schizophrenia, [16][17][18][19] Alzheimer's disease, 20 Huntington's disease, 21 Batten disease 22 and human brain tumors 23 (for detailed reviews on metabonomics, see Holmes et al 24 and Lenz and Wilson 25 ). These studies have identified a number of biochemical alterations that may be occurring as part of the pathogenesis of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have identified a number of biochemical alterations that may be occurring as part of the pathogenesis of these diseases. For example, Pears et al 22 identified glutamate and GABA alterations in aqueous brain extracts of a mouse model of Batten disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although many changes observed in neurological disorders are associated with specific neuroanatomical regions and are disease specific, certain metabolic changes are globally indicative of degeneration. The most common of these changes is a decrease in N-acetylaspartate (NAA) in brain tissues, which is indicative of neural loss and has been reported following AD, 41,48 HD, 79 -81 Rett's syndrome, 82 PD, 39,83 ALS, 36,37 multiple sclerosis, 23,84 Batten's disease, 85 and traumatic brain injury. 86 A summary of the key NMR spectroscopic-based studies in neurodegenerative disease and models of neurological disorders are listed in Table 1.…”
Section: Applications Of High-resolution Nmr Spectroscopy In Neurologmentioning
confidence: 99%